Corticosteroid-free immunosuppression in liver transplantation: An evidence-based review - Sgourakis, George (Baishideng Publishing Group Inc, 2014)
Thirty-six randomized controlled trials and two meta-analyses were reviewed. With respect to adult patients undergoing first orthotopic liver transplantation (OLT), steroid replacement resulted in fewer cases of overall acute rejection in the corticosteroid free-immunosuppression arm. Initial steroid administration for two weeks and early tacrolimus monotherapy is a feasible immunosuppression regimen without steroid replacement, although further investigations are needed in view of chronic rejections. No significant differences were noted between the treatment groups in terms of patient and graft survival independently of steroid replacement. Renal insufficiency, de novo hypertension, neurological disorders and infectious complications did not differ significantly among steroid and steroid-free groups. Diabetes mellitus, cholesterol levels and cytomegalovirus infection are more frequent in patients within the steroid group. With respect to diabetes mellitus and hypercholesterolemia, the difference was independent of steroid replacement. In relation to transplanted hepatitis C virus patients, mycophenolate mofetil does not appear to have a significant antiviral effect despite early reports. Male gender of donors and recipients, living donors, cold ischemia times, acute rejection, and early histological recurrence were related to the development of advanced hepatitis. There is sufficient scientific clinical evidence advocating avoidance of the ab initio use of steroids in OLT.